The Empire Bites Back: Sherlock Holmes as an Imperial Immune System - Laura Otis (Studies in 20th & 21st Century Literature, 1998)
Trained as a physician in the bacteriological age, Sir Arthur Conan Doyle created a detective-hero who acts both like a masterful bacteriologist and an imperial immune system. Doyle's experiences as a doctor in South Africa taught him that the colonies' microbes were his Empire's worst enemy. In 1890, Doyle visited Berlin, where Robert Koch was testing a "cure" for tuberculosis, and in Doyle's subsequent character sketch of Koch, the scientist sounds remarkably like Sherlock Holmes. Based on Doyle's medical instructor Joe Bell, Holmes shares Koch's relentless drive to hunt down and unmask tiny invaders. Imperialism, by the 1880s, had opened Europe to the peoples, cultures, and diseases of the lands it claimed. Holmes plays a defensive role, as an imperial intelligence network to detect foreigners "passing" in British society. The revenge, blackmail, and counterfeiting around which the Holmes stories are built reflect readers' anxieties about infiltration, about punishment for their colonial theft, and about the legitimacy of their own identity in a socio-economic system built on contradictions. Holmes thus responds to conflicting social demands, exposing interlopers who mimic traditional signs of respectability, and protecting "respectable" citizens from the consequences of their colonial crimes.
Keywords: bacteriological age; physician; Sir Arthur Conan Doyle; detective-hero; bacteriologist; imperial immune system; doctor; South Africa; colony; microbes; Empire; British Empire; Robert Koch; tuberculosis; cure; Sherlock Holmes; Joe Bell; Imperialism; cultures; disease; foreigners; passing; British society; revenge; blackmail; counterfeiting; Holmes stories; anxieties; infiltration; colonial theft; theft; legitimacy; identity; socio-economic system; colonial crimes